Activated platelet membrane nanovesicles recruit neutrophils to exert the antitumor efficiency - Shang, Yinghui; Sun, Juntao; Wu, Xin; Wang, Qinghai (Frontiers in Chemistry, 2022)
Platelets perform a crucial part in the recruitment of neutrophils, mediated by P-selectin, CCL5 and ICAM-2. In this study, we prepared platelet membrane nanovesicles from activated platelets. Whether activated platelet membrane nanovesicles can recruit neutrophils has not been reported, nor has their role in anti-tumor immunity. The results of SDS-PAGE showed that the platelet membrane nanovesicles retained almost all the proteins of platelets. Western Blotting showed that both the activated platelets and the platelet membrane nanovesicles expressed P-selectin, ICAM-2 and CCL5. In vivo results of mouse model of breast cancer transplanted tumor showed that tumor volume reduced significantly, Ki-67 positive tumor cells decreased, and TUNEL-positive tumor cells increased in tumors after treatment with activated platelet membrane nanovesicles (aPNs). After treated with aPNs, not only the number of neutrophils, CD8+, CD4+ T cells and B cells increased in tumor tissues, but also IL-12, TNF-α, and IFN-γ levels elevated significantly in tumor tissues.